Study The Relationship Between The Ability of Biofilms Formation and Antibiotic Sensitivity for Klebsiella pneumonia Isolated From Different Clinical Sources - Ali Hussein Alwan; Sura Mouaid Abas (College of Pharmacy / Mustansiriyah University, 2016)
Klebsiella pneumoniae is a dangerous pathogens that can cause severe diseases. The aim of this study is to examine the ability of K.pneumoniae to produce biofilms and the relationships between biofilms formation and antibiotics resistance. This study included isolation of 50 isolates of K.pneumoniae from different clinical sources from different hospitals in Baghdad city, the number and percentage of isolates according to the sources (urine, blood, sputum, burns, ear swabs, pus, wounds and stool ) were 22(44%), 11(22%), 4(8%), 4(8%), 3(6%), 3(6%), 2(4%) and 1(2%) respectively. Antibiotic sensitivity of the isolates was done by vitek 2 compact system using antibitics ( amikicin, azteronam, cefepime, ceftazidime, ciprofloxacin, gentamycin, impenem, meropenem, minocycline, piperacillin, piperacillin/ tazobactam, ticracillin, tobaromycin and trimethoprim/ sulfamethoxazole). The obtained results showed that the antibiotics amikicin, impenem and meropenem were more effective against the isolates. On other hand, the isolates showed different ability to produce biofilms according to the clincal sources was test by using two methods (Congo-red agar methods-CRA- and Tissue culture plate methods-TCP-), the results showed that the percentages of isolates formed biofilms in (CRA) 72% produce biofilms and 20% non productive and 8% non-specific. The percentages by TCP methods were 80% produce biofilms and 20% was not able to form biofilms. Higher production of biofilms isolates were exposed to Ciprofloxacin and Meropenem to make a comparison the antibiotic resistance between planktonic and biofilms producers isolates, the results showed that the resistance to antibiotics became 10 times higher than planktonic isolates. Form this study we can conclude that K.pneumoniae could be isolated from differents sources (that were multi-drug resistant) had the ability to produce biofilm in different methods